Multiple Traveling Salesman Problem menggunakan Algoritma Ant Colony Optimization dengan Operasi Elitism - Sugiarto Cokrowibowo; Ismail; Indra (Universitas Sulawesi Barat, 2020)
The Multiple Traveling Salesman Problem (MTSP) is a combinatorial optimization problem and extension of Traveling Salesman Problem (TSP). There are many implementation of MTSP on transportation and scheduling. MTSP is an NP-hard problem. This paper study about solving MTSP using Ant Colony Optimization and Elitisme operator from Genetic Algorithm. The result of this combination algorithm enhance the solution search performace because of the elitism operation which ensure the solution value always increase.